Improving Discipline Behavior through the Implementation of Reward and Punishment among Children Aged 4-5 Years - Andriani, Dessy; Effendi, Darwin; Maryani, Desy (Kumara Cendekia, 2026)
This study is a Classroom Action Research (CAR) based on the Kemmis and McTaggart model, conducted over two cycles involving 11 children aged 4–5 years.. The study aims to analyze the effectiveness of implementing reward and punishment methods in improving disciplinary behavior among children. Data were collected through observation using a disciplinary behavior assessment sheet based on TCP (Total Behavior Achievement) indicators—a total score representing the achievement of various established disciplinary behavior indicators. Initial observations during the Pre-Cycle stage showed low levels of disciplinary behavior, with an average TCP score of 18.5, placing the majority of children in the "Not Yet Developed" category. Following the implementation of reward and punishment strategies in Cycle I, the average TCP score increased to 30, with most children shifting to the "Starting to Develop" or "Developing as Expected" categories. A significant improvement continued in Cycle II, where the average TCP score reached 42.2, indicating that most children had achieved the "Developed Very Well" or "Developing as Expected" categories. The results demonstrate that the consistent and planned application of reward and punishment shows effectiveness within the context of the subjects and setting of this study in shaping disciplinary behavior in early childhood.